Vegetação e mecanismos de regeneração natural em diferentes ambientes da floresta ombrófila mista na flona de São Francisco de Paula, RS - Chami, Luciane Belmonte (2008)
This study evaluated the phitosociology of the Mixed Rain Forest and its mechanisms of regeneration (seeding banks, seed rain and soil seed bank). The data were collected in six conglomerates, being every one subdivided in 16 parcels of 20m x 20m. In the Chapter I it was studied the adult vegetation, where the tree and shrub species with circumference at the height of the chest equal or bigger than 30 cm were identified and measured. The species were classified in ecological groups and, on the basis of the density data, it was made an analysis of the grouping using the TWINSPAR method (Two-Way Indicattor Species Analysis). The groupings were characterized in relation to their horizontal structure. On the area, they 86 species were identified, being 18 pioneers, 25 secondary initials, 16 secondary delayed, 14 climax, and 13 were classified in more than one group. Three groupings were characterized (G1, G2 nd G3), in which gained special prominence the species Siphoneugena reitzii, Araucaria angustifolia and Sebastiania commersoniana, respectively in environments of hillside, of emergent trees and humid environments. In the chapter II based in the groupings formed in the adult vegetation, it was evaluated the mechanisms of regeneration. The seed rain was evaluated during the months of January to December of 2007, by means of the disposition of 96 collectors of 1 m2, in which it was observed the significant difference among the three groups in the quantity of seeds dispersed. In the study of the soil seed bank which was held through the collect of 5 cm of ground (taking out the burlap), it was observed that the group G1 showed significant difference in the quantity of storaged seeds in relation to groups G2 and G3. Seeding banks was showed in 72 showing unities of 2 m x 2 m, in which all the individuals with a size equal or bigger than 20 cm and DAP equal or lesser than 1 cm were identified and counted. The statistic analysis showed that, quantitatively, there was a significant difference among the three groups in relation to numbers of individuals in the seeding bank. For the joint analyses of the adult vegetation and mechanisms of regeneration, it is concluded, initially that the seeding bank, for having presented a bigger similarity with the vegetation, it can be the principal strategy of the maintenance of this forest. The seed rain is a basic strategy to the maintenance of the seeding bank. The seed bank didn´t present a flower potential for substituting the species present in the tree vegetation after alteration of the forest, being an essential strategy to the initial reestablishment of the area., due to the high density of the herbaceous plants. It was considered as tree basic species Araucaria angustifolia, Siphoneugena reitzii, llex brevicuspis, Podocarpus lambertii e Vernonia discolor, in hillside environments; Araucaria angustifolia, Casearia decandra, Blepharocalyx salicifolius, llex paraguariensis and Sebastiania brasiliensis in emergent tree environments; Araucaria angustifolia, Blepharocalyx salicifolius, Cryptocarya aschersoniana, llex brevicuspis, Sebastiania commersoinana e Siphoneugena reitzii in lands of bigger moistness. Through these informations one gives credit that such species will have greater possibility of stablishment in places with similar environment characteristics.